2008
DOI: 10.1111/j.1365-2184.2008.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity inhibits the proliferation and osteogenesis of rat bone marrow mesenchymal stem cells

Abstract: REFERENCE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…Exposure of rat bone marrow mesenchymal stems cells (rBMSC) to HMGE simulated microgravity study found that BMSC proliferation and osteogenesis decreased and the cells were growth arrested in the G0/G1 phase of cell cycle (Dai et al 2007). Data from their microarray (CapitalBio Corporation) analysis confirmed that rBMSC proliferation and osteogenesis gene activities decreased under simulated microgravity.…”
Section: Microarray Analysis Of Microgravity Exposed Other Cellsmentioning
confidence: 78%
“…Exposure of rat bone marrow mesenchymal stems cells (rBMSC) to HMGE simulated microgravity study found that BMSC proliferation and osteogenesis decreased and the cells were growth arrested in the G0/G1 phase of cell cycle (Dai et al 2007). Data from their microarray (CapitalBio Corporation) analysis confirmed that rBMSC proliferation and osteogenesis gene activities decreased under simulated microgravity.…”
Section: Microarray Analysis Of Microgravity Exposed Other Cellsmentioning
confidence: 78%
“…These results implied that abnormal F-actin reorganization and cell stiffness may result in decreased migration potentials of BMSCs. However, it has been reported that cells exposed to microgravity had depolymerized, extenuated, and dispersely distributed actin filaments (Dai et al 2007). Actually, the response of actin cytoskeleton to microgravity is complex and time dependent, and the reorganization of actin under simulated microgravity at different time points is not similar.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then trypsinized and counted by trypan blue exclusion. Cell doubling time (Td) was calculated according to the formula: Td = t×[lg2/(lgN t -lgN 0 )], where N0 is the number of cells inoculated, Nt is the number of cells harvested, and t is the culture time in hours (Dai et al, 2007).…”
Section: Population Doubling Timementioning
confidence: 99%